Facile synthesis of 5-aminoisophthalic acid functionalized magnetic nanoparticle for the removal of methylene blue - Qi, Lu; Jiaqi, Zou; Yimin, Dai; Danyang, Liu; Shengyun, Wang; Ling, Chen (Journal of materials science. Materials in electronics, 2020)
In this paper, a 5-aminoisophthalic acid (APTA) functionalized magnetic composite nanoparticles (Fe 3 O 4 @SiO 2 -APTA) are reported for adsorbing methylene blue (MB) from wastewater. The nanoparticles were analyzed by high resolution transmission electron microscopy, scanning electron microscopy, fourier transformed infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, N 2 adsorption/desorption, and vibrating sample magnetometer. The factors affecting the adsorption of methylene blue, initial concentration, adsorption time and pH of the solution were studied in detail. It was found that the adsorption capacity of magnetic composite nanoparticles depended on the pH of the solution. The results show that Fe 3 O 4 @SiO 2 -APTA exhibits an excellent adsorption performance with the maximum adsorption capacity (46.24 mg/g) for MB at pH 11. In addition, experimental results show that the adsorption of MB on Fe 3 O 4 @SiO 2 -APTA nanoparticles conforms to the pseudo-second-order kinetic model the Freundlich isotherm model, and reaches the adsorption equilibrium within 30 min. After consecutive use five times, adsorption percentages of MB were retained 70%, showing a good reusability of the adsorbent. The superior adsorption performances of Fe 3 O 4 @SiO 2 -APTA are attributed to electrostatic interaction, hydrogen bonding, and chemical sorption compared with recent adsorbents. Therefore, this work provides a promising approach for removal of MB with high efficiency, low cost.